Hans Vredeman de Vries - a ‘uomo universale’? [Hans Vredeman de Vries - ein ‘uomo universale’?] (Bulletin KNOB, 2001)
How is the artist Hans Vredeman de Vries to be characterized? Departing from the works of his comprehensive oeuvre that were passed down to us, this question was answered in various ways in art-historiography. Autobiographical statements of Vredeman himself will have to be brought in so as to make clear how he saw himself and what goal in life he pursued.Within his immense output of graphic work only five books comprise views of his own: on the one hand they are his books of columns from the years 1565 and 1578, in which Vredeman proposes ornamental variants for the five orders, referring to architectural theory and particularly to Vitruvius. On the other hand, at an advanced age he had presented two manuals, notably in 1577 ‘Architectura’ and in 1604/05 ‘Perspective’.Each of these two books comprises annotated texts and illustrations of a theoretical treatise. While in ‘Architectura’ Vredeman demonstrates his expertise in the field of architecture and his feeling for the requirements of practice, in ‘Perspective’ he proves his skills as a perspective painter. Vredeman's statements show that he wanted to compile the knowledge and experience gained throughout his life and present them as an orientation for the prescribed application of the arts.However, his personal interests are also involved in these publications: in the dedication of a French first edition of ‘Architectura’ to Prince William of Orange Vredeman is characterized as a careful architect of the Netherlands and an intelligent engineer. He offers his services for the reconstruction of the country after its destruction by the Spaniards.In an appendix to the French edition of ‘Architectura’, he mentions his qualifications as an architect and a perspective painter and refers to himself as a town planner. An example of the fact that Vredeman was interested in being equally active in the various disciplines can be found in an autobiographical document in Prague dating from 1598.Although at the imperial court of Rudolph II Vredeman mainly occupied himself with painting commissions, he was nevertheless called in for designs of buildings and fountains. Vredeman intended his career to be crowned by offering his practical and theoretical knowledge for the benefit of a university. His request at the University of Leiden in 1604 for a post in the field of perspective, engineering and architecture was rejected, however.Thus his scientific legacy is limited to the two manuals. An engraving from 1604 in the opening of the book on perspectives is the only visual representation of the artist definitely known so far: the 77-year-old Vredeman is depicted at a moment of reflection, notably on the theme of ‘Optica’.Hendrik Hondius posthumously enlarged this bust to a half-size portrait, which he published in ‘Theatrum Honoris’, a collection of portrayals of painters, in 1610. Unlike in the earlier engraving Vredeman is shown in action here, with a pair of compasses he is working at a geometrical design drawing. Especially the instrument of the compasses signifies that he is acquainted with the mathematically scientific principles of art. All this demonstrates that Vredeman was a ‘uomo universale’.